Assessment and Treatment of the Supplied Pipeline Water of Selected Areas of Dhaka City (Bangladesh Journal of Scientific and Industrial Research, 2010)
An investigation was carried out to assess the microbiological and physico-chemical characteristics of piped water supply of different areas of Dhaka City and the results were compared with the standard value of different organizations (i.e., WHO, DoE). The results revealed that microbiologically, 88.9% samples failed to ensure the standard level for drinking water due to the presence of TVB (total viable bacteria), TC (total coliform), TFC (total faecal coliform), TF (total fungal), Salmonella sp. and klebsiella sp. in the supplied water. However except turbidity other physico-chemical factors of supplied water were found satisfactory. Boiling for 5 minutes was found suitable for treatment of contaminated supplied water sample. Bleaching powder, sodium hypochlorite solution and Halotab were found suitable for the treatment of contaminated supplied water samples. Key words: Water, Assessment, Microbiological, Physico-chemical parameters, Disinfectant. DOI: 10.3329/bjsir.v44i3.4407 Bangladesh J. Sci. Ind. Res. 44(3),335-340, 2009